The Role of Saccharomyces cerevisiae and Streptococcus thermophilus Single Cell Proteins on the Growth of Common Carp Cyprinus carpio L.: J. K. Al-Farragi, M. J.Hindi and M. O. Muhyddin - Al-Farragi, J. K. (The Iraqi Journal of Veterinary Medicine, 2008)
The present investigation is concerned with utilizing of two types of Single Cell Protein (SCP) designated, Saccharomyces cerevisiae growth for processing P1. And joint growth of Saccharomyces cerevisiae with lactic acid bacteria Streptococcus thermophilus for processing P2. T2 and T3 respectively, as a replacemente of commercial animal protein T1 . The nutritional performance for SCP was carried out via feeding trials of carp fingerling Cyprinus carpio L.Values of fish weight rate for carp after 50 days of feeding triales started experiment were 1.15, 1.31, 1.34 gm. The fish growth rate were 0.425, 0.480, 0.500, gm .The averages of daily weight were 0.008, 0.009, 0.01gm/day , The absolute specific growth rates for fish were 0.92, 0.912, 0.932 for T1, T2 and T3, respectively, the statistical analysis showed high significant differences (P<0.01) among T1 and T3. The relative growth ratio was 58.62, 57.83, 59.52,Food conversion rates were 6.37, 6.56, 6.53, The food conversion efficiency 15.68, 15.16, 15.30, for T1, T2, T3, respectively, the statistical analysis showed insignificant differences (P<0.05) among T1, T2 and T3. The investigation concluded the possibility of utilizing SCP and this modest effort substitute commercial protein sources without adverse effect on the fish growth rate.